An advanced control of dual three-phase induction motor - BEDDA ZEKRI Ziad; GUERFI Djamal Eddine; MERAGHNI Abdelhai (University of Shahid Hama Lakhdar - El Oued, 2025)
Multiphase machines have gained significant attention in modern high-power applications due to their enhanced reliability and flexibility in power distribution. Among them, the dual three-phase induction machine presents notable advantages, as it incorporates two sets of three-phase windings within a single stator and is typically powered by dual voltage inverters. Recent research trends emphasize the integration of artificial intelligence techniques to boost the effectiveness and robustness of control strategies. This thesis focuses on the simulation-based analysis of field-oriented control based on the artificial neural networks (ANN-FOC) applied to a dual three-phase induction machine. شهدت الآلات متعددة الأطوار اهتمامًا مت ا زيدًا في التطبيقات الكهربائية عالية القدرة، بفضل موثوقيتها العالية وقدرتها على توزيع الطاقة بشكل أكثر مرونة. وتُعد آلة الحث ثلاثية الأطوار مزدوجة التغذية من أبرز هذه الآلات، حيث تحتوي على مجموعتين من اللفات الثلاثية موضوعة داخل نفس الجزء الثابت، ويتم تشغيلها بواسطة محولين للجهد. تُؤكد أحدث اتجاهات البحث على أهمية دمج تقنيات الذكاء الاصطناعي لتعزيز فعالية است ا رتيجيات التحكم ومتانتها. تُركز هذه الأطروحة على التحليل القائم على المحاكاة للتحكم الميداني، استنادًا إلى الشبكات العصبية الاصطناعية ) ANN-FOC (، والمُطبق على آلة حث ثنائية ثلاثية الطور.
Master's thesis in electromechanics.2025
Keywords: Multiphase machines; Dual three-phase induction machine; Field-oriented control (FOC); PI Controllers; ANN controllers.; آلات متعددة الأطوار، آلة الحث ثلاثية الأطوار مزدوجة التغذية، التحكم الموجه ميدانيًا ) FOC (، منظمات PI ، منظمات ANN